Analysis of 5-Year-old children's oral health service utilization and influencing factors in Guizhou Province, China (2019-2020) - Juanjuan Wu; Liming Chen; Min Guan; Taiming Dai; Reinhard E. Friedrich; Jiangling Sun; Wei Yang (BMC, 2023)
Abstract Background This study aimed to investigate the utilization patterns and factors related to oral health care for 5-year-old preschoolers based on Andersen's Behavioural Model in Guizhou Province, Western China. Method A cross-sectional study of 4,862 5-year-old preschoolers in 66 kindergartens was conducted in 2019 and 2020. A basic oral examination and a survey of parents and grandparents were conducted to gather data on oral health services. The results were analysed using chi-square tests and logistic regression analysis. Result The utilization rate of oral health services for children in Guizhou province was 20.5%. The dmft was 4.43, and the rate of caries was 72.2%. The average cost of a dental visit was higher in rural areas and higher for girls. Logistic regression analysis revealed that dmft ≥ 6 teeth, a history of toothache, starting toothbrushing at age ≤ 3 years and limited parental knowledge were the primary factors impacting dental visits. Conclusion Needs factors such as severe oral conditions and pain in children are the main reasons for the utilization of these services. This study underscores the urgency to actively promote the importance of oral health and expand insurance coverage for oral health services.